RELATIONSHIP BETWEEN NUMERICAL CAPABILITIES, INDEPENDENCE OF LEARNING AND PEERS WITH MATHEMATICS LEARNING OUTCOMES OF STUDENTS IN CLASS VIII - Retno Wulan Safitri; Abdul Taram (Universitas Ahmad Dahlan, 2018)
Low numeric ability and student independence learning, as well as among peers interaction are estimated with low mathematics obtained by students. The objective of this research is to know whether or not there is a correlation between numeric ability, independent learning, and peers with the result of mathematic at the 8th-grade students of Muhammadiyah Junior High School 3 Yogyakarta (SMP Muhammadiyah 3 Yogyakarta) in academic year 2016/2017. The population of this research is the 8th grades students of SMP Muhammadiyah 3 Yogyakarta. The sample of this research is taken using a random sampling technique to class, and obtained class VIII G as a sample class and VIII C as an experimental class. The data is taken from documentation, questionnaires, and test. The instrument uses validity and reliability. The data analysis uses prerequisite treatment include normality and independent treatment with the form of Chi-Square, linearity test using F-test formula, and hypothesis test using t-test. The result of the research showed that there is a positive and significant correlation between (1) numeric ability with the result of mathematics, with r = 0,6682 and ; (2) independent learning with the result of mathematics, with r = 0,4113 and ; (3) peers with the result of mathematics, with r = 0,3862 and ; (4) numeric ability and independent learning with the result of mathematics, with r = 0,4815 and and RC = , RC = and EC = , EC = ; (5) numeric ability and peers with the result of mathematics, with, r = 0,4520 and and RC = 92,9% , RC = 7,1% and EC = 41,7% , EC = 3,2% ; (6) independent learning and peers with the result of mathematics, with r = 0,2304 and and RC = 55,2% , RC = 44,8% and EC = 12,7% , EC = 10,3% ; (7) numeric ability, independent learning, and peers with the result of mathematics, with r = 0,4821 and and RC = 81,4%, RC = 16,5% ,RC = 2,1% and EC = 39,2% EC = 7,9% EC = 1,0 %.